Tokophobia: a fear of childbirth and pregnancy - an overview - Bhardwaj, Mudit; Sinwal, Aashutosh; Sharma, Vishv Sagar; Baby, Smrithimol; Singh, Shagun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Tokophobia is a mental disorder that affects women of all ages and varies from a mild to severe dread of delivery. Knauer first reported in the literature in 1897 that between 20% to 78% of pregnant women experience dread connected to pregnancy and delivery. The International Journal of Reproduction, Contraception, Obstetrics and Gynaecology published a study that found that the prevalence of tokophobia was 30.7% on Levin's scale and 55.3% on Areskog's score. Tokophobia is a multifaceted fear of labor that can be further classified into primary tokophobia and secondary tokophobia. People who have tokophobia may have extreme anxiety that manifests as nightmares, insomnia, panic attacks, and avoidance of situations involving pregnancy or childbirth. The most prevalent type of tokophobia is called secondary tokophobia, and it usually affects women who have already given birth and have experienced a traumatic delivery previously. A 20-item questionnaire called the fear of childbirth questionnaire (FCQ) is used to scale people's fear of giving birth. Cognitive-behavioral therapy (CBT) is mostly used as a non-pharmacological treatment.